Business Intelligence Agility, Informing Agility and Organizational Agility: Research Agenda - Skyrius, Rimvydas; Valentukevičė, Justina (Information & Media, 2020)
In assuring organizational agility, informing activities play a key role by sensing the environment for important changes. A special part has to be assigned to business intelligence (BI) activities, since their exact task is to monitor the environment and detect important issues to provide ground for well-informed responses. In turbulent business environment, BI function has to adjust dynamically to maintain the quality of produced insights. A survey on published research has shown that many sources stress the importance of agile BI on organizational agility in general. However, the importance of managerial and especially cultural factors for the role of informing in building up agility competencies is under-researched. The technology factors of agile informing that create preconditions for organizational agility are much better researched and evaluated than their human and managerial counterparts. There appears to be a need for consistent research approach in favor of the less researched human and managerial factors. The goal of this paper is to define research framework by addressing agility issues at three levels: organizational, information and BI agility. This framework is going to serve as a foundation for planned research on the factors of BI agility.